2014
DOI: 10.1371/journal.pone.0103992
|View full text |Cite
|
Sign up to set email alerts
|

Sequestering HMGB1 via DNA-Conjugated Beads Ameliorates Murine Colitis

Abstract: Inflammatory bowel disease (IBD) is chronic inflammation of the gastrointestinal tract that affects millions of people worldwide. Although the etiology of IBD is not clear, it is known that products from stressed cells and enteric microbes promote intestinal inflammation. High mobility group box 1 (HMGB1), originally identified as a nuclear DNA binding protein, is a cytokine-like protein mediator implicated in infection, sterile injury, autoimmune disease, and IBD. Elevated levels of HMGB1 have been detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…Taken together, the heightened cholinergic tone induced by EWS could be an important influence in modulating life-long enteric secretory diarrheal disease severity. In addition to regulation of intestinal ion transport, it has also become evident that the cholinergic nervous system plays a major role in the regulation of GI inflammation (71, 72, 77). For example, several investigations demonstrated that vagotomized animals exhibit exaggerated dextran sulphate sodium (DSS)-induced colitis and inflammatory cytokine responses, including IL-1β, IL-6, and TNF, compared with sham controls (78, 79).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, the heightened cholinergic tone induced by EWS could be an important influence in modulating life-long enteric secretory diarrheal disease severity. In addition to regulation of intestinal ion transport, it has also become evident that the cholinergic nervous system plays a major role in the regulation of GI inflammation (71, 72, 77). For example, several investigations demonstrated that vagotomized animals exhibit exaggerated dextran sulphate sodium (DSS)-induced colitis and inflammatory cytokine responses, including IL-1β, IL-6, and TNF, compared with sham controls (78, 79).…”
Section: Discussionmentioning
confidence: 99%
“…It is wellknown that the cholinergic nervous system is a major regulator of intestinal mucosal secretory mechanisms and barrier function and has received considerable attention as a critical modulator of intestinal inflammation. [67][68][69] Therefore, heightened cholinergic tone observed in EWS pigs and further investigation into the associated mechanisms could have significant impli-cations for a number of important GI diseases, especially GI diseases associated with ELA. For example, several studies have shown that cholinergic input plays a stimulatory role in infectious, secretory diarrhea as muscarinic cholinergic receptor blockade inhibited intestinal secretion induced by bacterial enterotoxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Approximately 1 in 150 people is affected with IBD in westernized nations and incidence is dramatically increasing in developing countries. 1,2 Approximately 1 in 150 people is affected with IBD in westernized nations and incidence is dramatically increasing in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that increased extracellular HMGB1 acts on epithelial and inflammatory cells, indicating an autocrine activity of the HMGB1 amplified in the intestine of IBD patients. Another study showed that infusing HMGB1 in the colon of mice resulted in a two-to threefold increase in LDH release, a marker of epithelial damage, further indicating that intraluminal HMGB1 induces tissue damage in the colon [51]. In addition, HMGB1 receptors such as TLR2 and TLR4 are also over-expressed in intestinal epithelial cells and active inflammatory cells in the intestinal mucosa of IBD patients [52].…”
Section: Hmgb1 Participates In a ''Positive Feedback Loop'' In The Inmentioning
confidence: 99%